Morbidity in Nigerian local cats after ileocolic valve or ileocolic valve and ileal resection (2011)
The morbidity of excision of the ileocolic valve (Group A), and the ileocolic valve with thirty percent (30%) distal ileal segments (Group B) were evaluated and compared in six adult local cats anaesthesized with xylazine (0.4 mg/kg) and ketamine hydrochloride (22 mg/kg). A non-significant fall (P>0.05) in the haemogram (PCV, Hb, RBC, and WBC), total serum proteins (albumin and globulin) and body weights were recorded among cats in groups A and B, following six weeks of post-operative monitoring. Samples of feces from both groups were non-bloody, non-mucoid and have normal to soft consistency with evidence of improvement over time. The improvement in fecal consistency, body weight and haematological picture over the period of post-operative management was adjudged to be consistent with adaptive changes in the residual intestinal segments. The observed clinical features are discussed in relation with those of massive intestinal resection in cats, dogs and humans. It was concluded that ileocolic valve resection produced little or no detrimental effects on bowel functions of local cats, and local cats could tolerate ileocolic valve with thirty percent (30%) distal ileal resection provided the proximal intestinal segments are intact